PROFILE INDUSTRI KREATIF ANIMASI 2D DI SLEMAN, YOGYAKARTA - Yuhanto, Priya Wintar (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
The creative animation industry is an industry that originates from the utilization of creativity, skills and individual talents to create animated works which in turn can produce welfare and employment by exploring the individualâ€™s creative and creative abilities. This can be interpreted as a collection of activities related to the creation or use of knowledge and information that produces animated works. Sleman, Yogyakarta which is a city of education and city of culture has a large potential of creative human resources (HR), as evidenced by theÂ success of the wide screen animated film â€œBatlte of Surabayaâ€ by MSV Picture, â€œHome Landâ€ by the Invisible Studio Studio by Sleman animators, Yogyakarta. The Ministry of Industry in the Communication Forum for Telematics Strengthening in Yogyakarta has launched Yogyakarta as one of the embryo cities of the creative animation industry in Indonesia in addition to Bali, Jakarta, Semarang and Pacitan. The purpose of the research is to review the profile of the creative creative industry in Yogyakarta (especially the Sleman area). By using qualitative descriptive analysis, it can be seen the picture of the creative creative industry profile in general in Sleman, Yogyakarta. The results of this study indicate that most 2D animation studio profiles in Sleman are quite good, this is shown from the data of formal and non-formal education working in the animation industry in accordance with their competencies, namely graduates of animation, multimedia and DKV vocational schools. The work is quite numerous and of high quality. The results of this analysis are expected to provide recommendations for conducting a strengthening agenda for the 2D animation creative industry, so that the competitiveness and productivity of the creative animation industry in Sleman Yogyakarta can be improved.